ISSUES OF IMPROVING THE SUSTAINABILITY RATING OF BUSINESS ENTITIES (American Journal of Business Management, Economics and Banking, 2026)
Entrepreneurial activity represents the cornerstone of economic development and transformation in any modern society. The sustainability of entrepreneurial entities, both large and small, plays a decisive role in ensuring a stable market environment and fostering long-term growth. Thus, the improvement of sustainability ratings for entrepreneurial subjects requires a thorough analysis of current practices, the identification of key factors affecting stability, and the development of viable mechanisms that enhance resilience and competitiveness in dynamic conditions.